Analysis of Students Critical Thinking Skills in Conventional Learning - Wardani, Miessya; Feronika, Tonih; Ardianti, Dewi Linda (LAVOISIER: Chemistry Education Journal, 2024)
Student-centered learning significantly influences students' learning and thinking abilities. However, in practice, many teachers still use conventional teaching methods, such as lectures, to deliver material. Conventional teaching is often chosen because it can quickly convey information and is easy to implement in the learning process. Learning activities are a process for students to enhance their abilities and skills. One of the essential skills students need to develop is critical thinking. This skill can foster cognitive aspects and improve students' problem-solving abilities. Critical thinking skills can be trained during learning activities. This study aims to determine students' critical thinking skills in conventional learning on hydrocarbon combustion. The research employs a descriptive quantitative method with a test instrument in the form of essay questions. Ennis's critical thinking aspects measure students' critical thinking skills. Ennis's critical thinking aspects consist of 5 aspects encompassing 12 indicators. The results of the study show that students' critical thinking skills in conventional learning are categorized as low with 52.80%.